Genius azerbaijani teacher Gafur Rashad Mirzazada. (Journal of Educational Sciences, 2016)
The theme of the article is about pedagogical activity and educational view of the Azerbaijan pedagogue Qafur Rashad Mirzazadeh. The issues of education are generalized in his works.
Keywords: history of education; textbooks; education; scholar; educator; children’s literature